Preimplantation genetic testing (PGT) for hemophilia A: Experience from one center - Thi Minh Phuong Bui; Van Khanh Tran; Thi Thanh Hai Nguyen; Thi Phuong Le; Thi Mai Nguyen; Hai Anh Tran; Vu Dung Luu; Manh Ha Nguyen; The-Hung Bui; Thanh Van Ta; Thinh Huy Tran (Elsevier, 2022)
Objective: Hemophilia A (HA) is an X-linked recessive bleeding disease caused by a deficiency or dysfunction of blood coagulation factor VIII (FVIII). Available treatment to replenish the missing factor may not reach a good outcome for all patients because of potential complications that include the development of inhibitor antibodies directed against factor VIII. Therefore, the prevention of transmitting pathogenic mutations to the next generation is the best solution for this disease. Preimplantation genetic testing for a monogenic disorder (PGT-M) has become a standard method to prevent the transmission of monogenic heritable disease. The gold standard of the molecular technique used for PGT-M nowadays is the co-amplification of the polymorphic microsatellite linkage markers that use microsatellite DNA technique that overcomes the limitation of other methods. The important issue of this technique is the definition of markers that are specific for each allele on different loci. Each gene locus needs a characteristic design to allow accurate diagnosis that can be applied on PGT-M due to the limited quantity of DNA available. Here we present our study of four specific self-designed linked polymorphic markers applied on screening the embryos before implantation for hemophilia A families in Vietnam. Material and methods: In this study, we investigated the feasibility of application and diagnostic value of 4 STR loci (FXS1108, DXS9897, F8int22, DXS9901) in the intragenic or neighbouring regions of the F8 gene. 35 hemophilia A families were recruited for STR analysis to define at least two characteristic heterologous markers for each family and 12 cases of pre-implantation genetic testing (PGT-M) for carrier mothers were performed. Result: All 4 of these loci (FXS1108, DXS9897, F8int22, DXS9901) were found practical and useful for preimplantation genetic testing (PGT-M). All 12 cases of PGT-M using the method had informative STR results and correct diagnosis was achieved. 9 out of the 12 mothers (75%) were implanted with 1-2 thawed embryos after the biopsy resulting in the birth of 5 healthy babies (55%). Conclusion: We conclude that specific 4 STR markers for rapid pre-implantation genetic testing of hemophilia A can be successfully applied with high confidence and accuracy in clinical settings. The results of the study provide solid evidence confirming that the microsatellite DNA technique is a highly reliable method, suitable for hemophilia A families wishing to determine carrier status or having healthy babies.